The gap in capacity building on climate, health, and equity in built environment postsecondary education: a mixed-methods study - Houghton, Adele (Frontiers in Public Health, 2023)
Institutions of higher education are feeling increasing pressure from both students and the international climate community to offer more courses and joint degrees on the role of the built environment in advancing climate action, population health, and social equity. The built environment plays a leading role in this new, transdisciplinary approach. Thoughtfully designed buildings, neighborhoods, and communities can simultaneously lower per capita greenhouse gas emissions, reduce population exposure to dangerous climate-sensitive extreme weather events, reduce disparities in climate-related health outcomes, and advance social equity goals. This mixed-methods study explored the extent to which post-secondary courses and joint degree programs teach students the research methods and technical skills they will need to design and implement built environment interventions addressing the effects of climate change on population health and social equity. The study found that the number of universities offering courses addressing climate, health, and equity in the built environment grew from 2018 to 2022. The number of joint planning/public health degree programs rose from four in 2005 to 15 in 2022. No joint architecture/public health degree programs were identified. A detailed review of 99 course descriptions from three universities found that 17 courses (roughly 1/5 of the total) covered population health, built environment, and climate change; and, 2/3 of the set (n = 60) covered two out of the three topics. Schools of public health were more likely to offer courses covering all three topics, whereas schools of architecture were more likely to include the building scale in relevant courses. Exposure pathways and social equity/vulnerable populations were the most common methods included in relevant courses. Professors and administrators at institutions identified by the study as “transdisciplinary-ready” reported that accreditation requirements and university rules governing the allocation of student tuition had slowed efforts to offer cross-listed courses. However, faculty in these institutions regularly collaborate informally with their peers – both on transdisciplinary research and by offering guest lectures in each other’s courses. The results of this study show that, while universities have made great strides over the past 18 years in beginning to support transdisciplinary research and pedagogy, institutional barriers and gaps in key content areas remain.